證明:如圖1,過點E作EH∥AB交AC于點H.
則∠BAC+∠AHE=180°,∠BAC=∠CHE,
∵AB=BC=AC,
∴∠BAC=∠ACB=60°,
∴∠CHE=∠ACB=∠B=60°,
∴EH=EC.
∵AD∥BC,
∴∠FCE=180°-∠D=120°,
又∵∠AHE=180°-∠BAC=120°,
∴∠AHE=∠FCE,
∵∠AOE=∠COF,∠AEF=∠ACF,
∴∠EAC=∠EFC,
在△AEH和△FEC中,
∵
|
∴△AEH≌△FEC,
∴AE=EF;
(2)猜想:(1)中的結論是沒有發(fā)生變化.
![](http://hiphotos.baidu.com/zhidao/pic/item/adaf2edda3cc7cd99a6b5e5b3a01213fb90e91e9.jpg)
證明:如圖2,過點E作EH∥AB交AC于點H,則∠BAC+∠AHE=180°,∠BAC=∠CHE,
∵AB=BC,
∴∠BAC=∠ACB
∴∠CHE=∠ACB,
∴EH=EC
∵AD∥BC,
∴∠D+∠DCB=180°.
∵∠BAC=∠D,
∴∠AHE=∠DCB=∠ECF
∵∠AOE=∠COF,∠AEF=∠ACF,
∴∠EAC=∠EFC,
∴△AEH≌△FEC,
∴AE=EF;
(3)猜想:(1)中的結論發(fā)生變化.
證明:如圖3,過點E作EH∥AB交AC于點H.
由(2)可得∠EAC=∠EFC,
∵AD∥BC,∠BAC=∠D,
∴∠AHE=∠DCB=∠ECF,
∴△AEH∽△FEC,
∴AE:EF=EH:EC,
∵EH∥AB,
∴△ABC∽△HEC,
∴EH:EC=AB:BC=k,
∴AE:EF=k,
∴AE=kEF.